Innovation and Change Management in the Publishing Industry: Adapting to Digital Transformation - Liu, Wenjie (Transactions on Social Science, Education and Humanities Research, 2023)
This study explores the importance of innovation and adept change management within the publishing industry amidst the significant digital transformation underway. Through comprehensive literature review and analysis of case studies, the paper underscores the necessity for innovation in publishing, elucidating various forms such as technological, process, and product innovations. The study further highlights the crucial role of effective change management strategies, leadership commitment, and conducive organizational culture in facilitating a smooth transition through digital disruptions. Examining the impact on various stakeholders, including authors, readers, and publishers, this paper provides insights into the challenges and opportunities presented by digital transformation. Moreover, it offers a glimpse into the future of digital publishing, spotlighting emerging trends and their implications. The findings are instrumental for industry stakeholders to navigate the digital landscape effectively, leveraging insights for strategic innovation and change management in the evolving publishing environment.